2007
DOI: 10.1136/jcp.2007.047647
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood culture contamination in adults and venepuncture technique: prospective cohort study

Abstract: Compliance with a hospital protocol on PBC collection technique in adults significantly reduces blood culture contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 20 publications
1
13
0
2
Order By: Relevance
“…The overall blood culture contamination rate in this study, 4%, lies within the wide range (0.42% to 15.1%) reported previously for various settings (1,2,4,10,11,15,19,24,31,32,34,38) and is close to that of other ICU populations (5.5% [7]). The overall blood culture rate of detection of true pathogens is similarly consistent with those reported previously for other ICU patient series, 4.6% (7) to 12.8% (21).…”
Section: Discussionsupporting
confidence: 48%
“…The overall blood culture contamination rate in this study, 4%, lies within the wide range (0.42% to 15.1%) reported previously for various settings (1,2,4,10,11,15,19,24,31,32,34,38) and is close to that of other ICU populations (5.5% [7]). The overall blood culture rate of detection of true pathogens is similarly consistent with those reported previously for other ICU patient series, 4.6% (7) to 12.8% (21).…”
Section: Discussionsupporting
confidence: 48%
“…In addition, after the application of PI to the patients' skin, the need to wait for at least 30 s or more beside a patient in distress might occasionally be stressful for caring physicians, especially in acute-care settings, even if they know the necessity of the waiting time. Indeed, Qamruddin et al reported a rate of compliance with the protocol of as low as 30% among the phlebotomists in their study (20). Simple and easy procedural protocols will likely increase the rate of compliance with the protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the reported rates of contamination vary from 0.8% to over 8% among institutions. Almost half of all positive results were reported to be contaminants at some institutions (1,4,15,18,20,23,24,26,31). With such a high contamination rate, it is not easy to interpret the results properly for clinicians.…”
mentioning
confidence: 99%
“…Mientras otras publicaciones destacan al Staphylococcus coagulasa negativo como principal microorganismo aislado mediante el uso de hemocultivos [14,20,33,49]. La heterogeneidad en el marco metodológico de cada estudio, el tamaño de la población evaluada y el contexto clínico de referencia permiten comprender la variabilidad de los resultados bacteriológicos obtenidos a nivel internacional con respecto al aislamiento de microorganismos en este trabajo de investigación [15,18,19,20].…”
Section: Discussionunclassified
“…Existe amplia evidencia publicada sobre las prácticas que mejoran la sensibilidad de este estudio [2,18,21,24,[32][33][34], disminuyen la tasa de contaminación de la muestra [33][34][35][36][37][38][39] y los accidentes laborales [26]. Sin embargo, la documentación institucional oficial que resume las recomendaciones para la toma correcta del hemocultivo puede no tener la difusión suficiente entre el personal responsable de esta labor [40].…”
Section: Discussionunclassified